Instrument wiring & grounding ([S.l.] : Fisher Controls International, 1989)
These two videos contains two parts. Part 1 discussed on electrical noise, AC power wiring, DC power wiring and ground power wiring. Part 2 discussed on field wiring, grounding practices, data highways
part 1 AC/DC power and ground wiring - part 2 Signal wiring and shielding
Copy available in DVD format
Keywords: Power (Mechanics); Electric wiring